PENERAPAN QUALITY FUNCTION DEPLOYMENT (QFD) UNTUK MENINGKATKAN KUALITAS LAYANAN JASA KOPERASI (Studi pada KSPPS TAZAKKA Bojong) - Sobirin, Achmad; Kusumawardhani, Amie (Diponegoro Journal of Management, 2017)
KSPPS TAZAKKA Bojong is one of sharia financial services cooperatives (KJKS) which was established in Bojong District, Pekalongan Regency. The growing number of cooperatives nowadays in Bojong sub-district has made the competition tighter so that the growth target of customers is not achieved and there is a decrease in the financing partners. One way to win the competition is by improving the quality of service continuously to fit the expectations of costumers. This study discusses the application of Quality Function Deployment (QFD), which aims to determine customersâ€™ needs so that each functional area and organization / company level can act towards existing functional services.Data in this research was collected by survey method with questionnaire tool to KSPPS TAZAKKA Bojong manager and 50 cooperative customers as respondents. This Study appliedÂ  method used is the Quality Function Development (QFD) Method.The research showed the priority scale of customer requirements that should be prioritized in the improvement of the service that is the customer requirements of the company's credibility and reputation of the company. This research also showed the sequence of technical attributes of KSPPS TAZAKKA Bojong in order to satisfy the customer that si The technical attribute of routine briefing for excellent service obtained from the calculation of absolute weight and relative weight.